IMPACT OF CHANGES IN CLIMATE AND LAND USE ON THE FUTURE STREAMFLOW FLUCTUATION - Suria Tarigan; Akhmad Faqih (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Beside land use change, future climate change potentially alters streamflow fluctuation of a river basin in Indonesia. We investigated relative impact of changes in climate and land use on the streamflow fluctuation of a watershed for future condition (2025). To account for the climate change, we simulated future rainfall and temperature scenarios using the downscaled rainfall and mean surface temperature of 24 CMIP5 GCM outputs with moderate scenario of RCP4.5. We used distributed hydrologic model (SWAT) to simulate relative impact of changes in climate and plantation expansion on the future streamflow fluctuation. The SWAT model performed well with the Nash-Sutcliff efficiency values of 0.80-0.85 (calibration) and 0.84-0.86 (validation). The results indicated that the climate change caused 32% decrease of the low flows during dry season and 96% increase of the flooding peak discharge during rainy season. Meanwhile, the plantation expansion led to 40% decrease of the low flow in the dry season and 65% increase of the flooding peak discharge in wet season. Both changes indicated strong impact on the extreme events such as flooding peak discharge and low flows. The impact of the climate change on the increased peak discharge was stronger compared to that of land use change. Meanwhile, the impact of the land use change on the low flow was stronger compared to that of the climate change. The results of this study pointed out that both climate change and the plantation expansion potentially become crucial factors for the future water security in Indonesia.